(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
The geographical positioning of coastal Bangladesh makes it more exposed to cyclonic events. Building cyclone shelters is a vital strategy for reducing the risk of natural hazards in the coastal area of Bangladesh. But often they are not easily accessible and well facilitated. This paper aims to assess the accessibility of current cyclone shelters in six upazilas of the coastal region of Bangladesh. AccessMod 5 tool was used to simulate travel time to cyclone shelters, providing insights into shelter accessibility and aiding in identifying areas requiring infrastructural improvements. Referral analysis was used to calculate optimal routes and travel times between starting points and cyclone shelters and zonal statistics to assess areas or populations within specific travel times to shelters. The coverage analysis for the study area was carried out to shed light on the existing coverage of cyclone shelters across its districts. Cyclone shelters in the southeast of the study area have longer travel times due to limited road accessibility; which makes delays for 30 to 60 minutes. People can reach cyclone shelters within 30 minutes in Char Fassion. In comparison, Barguna Sadar poses challenges, especially within the one-hour criterion. While some unions show reasonable accessibility metrics, others, particularly in the southeast, highlight the urgent need for infrastructure and strategic improvements to ensure optimal cyclone shelter accessibility. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(2), 2024, P 63-75